T cell-independent eradication of experimental glioma by intravenous TLR7/8-agonist-loaded nanoparticles - Turco, Verena; Pfleiderer, Kira; Hunger, Jessica; Horvat, Natalie; Karimian-Jazi, Kianush; Schregel, Katharina; Fischer, Manuel; Brugnara, Gianluca; Jähne, Kristine; Sturm, Volker Jörg Friedrich; Streibel, Yannik; Nguyen, Duy; et al. (Nature Communications, 2023)
Glioblastoma, the most common and aggressive primary brain tumor type, is considered an immunologically “cold” tumor with sparse infiltration by adaptive immune cells. Immunosuppressive tumor-associated myeloid cells are drivers of tumor progression. Therefore, targeting and reprogramming intratumoral myeloid cells is an appealing therapeutic strategy. Here, we investigate a β-cyclodextrin nanoparticle (CDNP) formulation encapsulating the Toll-like receptor 7 and 8 (TLR7/8) agonist R848 (CDNP-R848) to reprogram myeloid cells in the glioma microenvironment. We show that intravenous monotherapy with CDNP-R848 induces regression of established syngeneic experimental glioma, resulting in increased survival rates compared with unloaded CDNP controls. Mechanistically, CDNP-R848 treatment reshapes the immunosuppressive tumor microenvironment and orchestrates tumor clearing by pro-inflammatory tumor-associated myeloid cells, independently of T cells and NK cells. Using serial magnetic resonance imaging, we identify a radiomic signature in response to CDNP-R848 treatment and ultrasmall superparamagnetic iron oxide (USPIO) imaging reveals that immunosuppressive macrophage recruitment is reduced by CDNP-R848. In conclusion, CDNP-R848 induces tumor regression in experimental glioma by targeting blood-borne macrophages without requiring adaptive immunity.
Gesehen am 28.09.2023